DEMAND FORECASTING: A CASE STUDY OF THE INDONESIAN TOBACCO INDUSTRY - Bagaskara, Hilman; Fajri ananda, Candra (Contemporary Studies in Economic, Finance and Banking, 2024)
The tobacco industry, as one of the major industries in Indonesia, has experienced consistent growth. Despite being burdened by stringent regulations; tobacco products still maintain high demand among consumers. Forecasting serves as a crucial tool for every industry, aiding in decision-making and planning. ARIMA is one of the reliable forecasting methods, yet it remains open for further development. This study aims to compare ARIMA and SARIMAX, which incorporates seasonal aspects and external variables, namely weighted tariffs and affordability, to determine which of these forecasting models is more accurate. Through the execution of the equations, this research has demonstrated that SARIMAX outperforms ARIMA with a lower Mean Absolute Percentage Error (MAPE) score of 7.63 compared to ARIMA's more accurate MAPE score of 10.8. These findings indicate that SARIMAX is more accurate, as evidenced by its lower MAPE score of 7.63.